Impacts of adaptation to climate change on farmers' income in the Savana region of Togo - Pilo Mikémina; Nicolas Gerber; Tobias Wünscher (University of Bonn, Center for Development Research (ZEF), 2018)
West African farmers are among those most likely to suffer from climate change, partly due to the agro-climatic characteristics of the regional system and to their limited scope for coping with shocks. Climate change adaptation has thus been touted as a necessary path for rural poverty reduction and development in the region. Yet, do farm households who implemented climate change adaptation earn higher income compare to those who did not? We attempt to answer this question in the context of crop and livestock income in the Savana region of Togo. To that end, we build a bio-economic model based on farm household model theory. Using survey data collected from a representative sample of 450 savanna farm households of the agricultural year 2014/2015, we identify farm-household types through cluster analysis and apply them in the simulation model. From the simulation results, we conclude that at their current costs, soil and water conservation techniques and irrigation practives can on average provide higher income even under climate change, since they are able to mitigate at least 63% of the impacts of climate change on crop and livestock income. By contrast, reducing the quantity of applied fertilizer, mentioned as an adaptation option by farmers, increases the farm households' vulnerability to climate change. The policy message we draw from this study is to encourage Soil and Water Conservation techniques and sustainable irrigation as sound strategies for higher income under climate change in the region. These are "no regret options" with a positive impact on livelihoods while preserving the resource base.
Keywords: 330; adaptation; bio-economic model; Savana region of Togo